An automated pattern recognition system for classifying indirect immunofluorescence images of HEp-2 cells and specimens. (March 2016) - Manivannan, Siyamalan; Li, Wenqi; Akbar, Shazia; Wang, Ruixuan; Zhang, Jianguo; McKenna, Stephen J.
Abstract: Immunofluorescence antinuclear antibody tests are important for diagnosis and management of autoimmune conditions; a key step that would benefit from reliable automation is the recognition of subcellular patterns suggestive of different diseases. We present a system to recognize such patterns, at cellular and specimen levels, in images of HEp-2 cells. Ensembles of SVMs were trained to classify cells into six classes based on sparse encoding of texture features with cell pyramids, capturing spatial, multi-scale structure. A similar approach was used to classify specimens into seven classes. Software implementations were submitted to an international contest hosted by ICPR 2014 (Performance Evaluation of Indirect Immunofluorescence Image Analysis Systems). Mean class accuracies obtained on heldout test data sets were 87.1% and 88.5% for cell and specimen classification respectively. These were the highest achieved in the competition, suggesting that our methods are state-of-the-art. We provide detailed descriptions and extensive experiments with various features and encoding methods. Abstract : Highlights: We propose systems for classifying immunofluorescence images of HEp-2 cells. Images are classified at both the cell level and the specimen level. Ensemble SVM classification based on sparse coding of texture features was effective. Cell pyramids and artificial dataset augmentation increased mean class accuracy. The proposed systems came first in the I3A contest associated with ICPR 2014.